PRINSIP NILAI MANAJEMEN PENDIDIKAN ISLAM PERSPEKTIF AL QUR’AN: Kajian Tematik Ayat-ayat Manajemen Pendidikan - Lutfi, Muhammad (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2023)
The aim of this study is to provide an analysis related to educational management from the perspective of the Qur’an. This study uses a qualitative approach with the type of library research, namely collecting data that is literary as the object of research. The results of the study show that education management should refer to the principles of the Qur'an which include: faith, sincerity, kindness, exemplary, unity of direction, deliberation, accountability, efficient and effective, participatory, responsible, competent, and cooperative and flexible